Development of Science Learning Media Klanimal Android-Based for Elementary School Students - Fadhilah Nur Lailatus Saadah; Fitria Nur Hasanah (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
The difficulties students face in understanding the concepts of Science are due to their abstract nature, making it difficult to retain long-term memory. The research objective is to develop an interactive Android-based media to visualize Science learning, specifically the concept of animal classification based on their types of food, to facilitate its retention in students' long-term memory. The "Klanimal" media is an Android-based platform that includes content menus, learning objectives menus, animal guessing menus, and quiz menus. The research methodology employed in this study is the Research and Development (R&D) approach. The development model used is the ADDIE development model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. Media experts and subject matter experts validated the Klanimal media. Subsequently, it was tested on 6th-grade students. The test results showed a percentage of 89.8, indicating a highly suitable category. Pretest and post-test scores improved, and the N Gain analysis indicated a value of 0.70, indicating a significant increase in understanding. The research findings suggest that the effective use of Android-based Science learning media enhances the understanding of 5th-grade students at SDN Candibinangun IV Sukorejo, specifically regarding the topic of animal classification based on their types of food.